Il linguaggio del trauma, poesia e ripetizione. Tradurre Elegie del Quattro giugno di Liu Xiaobo - Pesaro, Nicoletta (L’ospite ingrato, 2025)
Translation is an act of repetition. Translating the poetry collection Niannian liusi 年年六四 (June Fourth Elegies) by Nobel Peace Prize laureate Liu Xiaobo 刘小波 – who passed away in 2017 under a surveillance regime after many years of imprisonment – is an act of repetition and preservation of trauma. The poems in the collection, written annually on the anniversaries of the Tian’an men Square massacre from 1990 to 2009, form a «lyrical synthesis of rare balance» between political denunciation and ritual song, offering a poetic sharing of human suffering. This paper examines the primary strategies employed in the Italian translation of the collection (Lantana, 2013) and explores the text’s meaning in relation to trauma, as well as the contradiction between poetry/translation as a compulsion to relive trauma and poetry/translation as a means of salvation from oblivion.